Pengaruh Self-Acceptance dan Self-Depriciation Terhadap Irrational Belief Pada Siswa Dengan Hasil Belajar Rendah - Amirah, Nadiratul; F, Firman; N, Netrawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Self-acceptance and self-deprecation are two forms of self-evaluation that have a significant influence on the formation of irrational beliefs in students, especially students with low learning outcomes. Self-acceptance reflects an individual’s acceptance of themselves as a whole, including shortcomings and failures. While self-depreciation is a tendency to belittle themselves and judge themselves negatively. This study aims to examine theoretically the influence of self-acceptance and self-depreciation on irrational beliefs in students who experience academic difficulties. Through literature reviews and findings from various empirical studies, it is known that students with high levels of self-acceptance tend to have rational beliefs and can face failure healthily. However, students with high self-depreciation are more prone to developing irrational beliefs such as feeling unworthy, fearing rejection and absolutist thinking. These findings emphasize the importance of a psychological approach that supports self-acceptance in counseling interventions to reduce irrational beliefs and improve students’ academic mental health.